Use cases, best practice and reporting standards for metabolomics in regulatory toxicology - Viant, MR; Ebbels, TMD; Beger, RD; Ekman, DR; Epps, DJT; Kamp, H; Leonards, PEG; Loizou, GD; Macrae, JI; Van Ravenzwaay, B; Rocca-Serra, P; Salek, RM; et al. (Nature, 2019)
Metabolomics is a widely used technology in academic research, yet its application to regulatory science has been limited. The most commonly cited barrier to its translation is lack of performance and reporting standards. The Metabolomics standaRds Initiative in Toxicology (MERIT) project brings together international experts from multiple sectors to address this need. Here, we identify the most relevant applications for metabolomics in regulatory toxicology and develop best practice guidelines, performance and reporting standards for acquiring and analysing untargeted metabolomics and targeted metabolite data. We recommend that these guidelines are evaluated and implemented for several regulatory use cases.